Hubungan Penggunaan Gadget Dengan Tumbuh Kembang Balita Di Desa Kepala Sungai Kec. Secanggang Kab. Langkat Tahun 2022 - Maysarah, Dede; Mardiah, Mardiah (Innovative: Journal Of Social Science Research, 2024)
Continuous use of gadgets will have a negative impact on children's thought patterns and behavior in their daily lives, children who tend to continuously use gadgets will be very dependent and become a routine activity in their daily activities, in this case children are often more choosing to play with gadgets causes children to become lazy about moving and doing activities. The use of gadgets among children is increasingly worrying and certainly has a negative impact on growth and development. The aim of this research is to determine the relationship between gadget use and the growth and development of toddlers in Head Sungai Village, Kec. Secanggang District. Langkat 2022. This type of research uses correlational methods. Population of 30 children in Head River Village, Kec. Secanggang district. Step up. Sample of 30 respondents with total sampling method. The independent variable is the use of gadgets and the dependent variable is the growth and development of toddlers. Measured by questionnaire and child DDST. The data analysis technique uses the chi-square test. The results of the research showed that of the 30 respondents studied, it was found that the majority of the respondents were 10 children who often used gadgets with normal growth and development, while there were 2 minority children who often used gadgets with normal growth and development (2). 6 .6%). Based on the majority of children who sometimes play with gadgets with growth and development, approximately 5 people (16.6%), while minority children sometimes use gadgets with growth and development, there are approximately 1 person (3.3%). Based on the majority of children who never use gadgets with normal growth and development, there are 3 people (10%), while the minority children who use gadgets never have sufficient growth and development and the number is less than 0 (0%). It is hoped that parents can limit children's use of gadgets and can supervise the activities carried out by children when playing with gadgets.